2011
DOI: 10.1002/dvdy.22673
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage and microglia ontogeny in the mouse visual system can be traced by the expression of Cathepsins B and D

Abstract: Here, we show a detailed chronotopographical analysis of cathepsin B and D expression during development of the mouse visual system. Both proteases were detected in large rounded/ameboid cells usually located in close relationship with prominent sites of extensive physiological cell death. In concordance with their morphological features and topographical distribution, we demonstrate that expressing cells corresponded with macrophages and microglial precursors. We found that as microglial precursors differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 108 publications
1
58
0
Order By: Relevance
“…Notice that presumptive retinal pigment epithelium (pRPE) was also faintly stained with SA-β-GAL ( Figure 1A,C,E,G). 51 Using immunohistochemical techniques against cathepsin-D (CatD), an enzyme that identifies the distribution of lysosomes in the vertebrate developing retina, 19,20 we found that the SA-β-GAL histochemical staining pattern correlates strongly in the presence of lysosomes in the NbL of the central retina ( Figure 1I-K). 51 Using immunohistochemical techniques against cathepsin-D (CatD), an enzyme that identifies the distribution of lysosomes in the vertebrate developing retina, 19,20 we found that the SA-β-GAL histochemical staining pattern correlates strongly in the presence of lysosomes in the NbL of the central retina ( Figure 1I-K).…”
Section: Resultsmentioning
confidence: 99%
“…Notice that presumptive retinal pigment epithelium (pRPE) was also faintly stained with SA-β-GAL ( Figure 1A,C,E,G). 51 Using immunohistochemical techniques against cathepsin-D (CatD), an enzyme that identifies the distribution of lysosomes in the vertebrate developing retina, 19,20 we found that the SA-β-GAL histochemical staining pattern correlates strongly in the presence of lysosomes in the NbL of the central retina ( Figure 1I-K). 51 Using immunohistochemical techniques against cathepsin-D (CatD), an enzyme that identifies the distribution of lysosomes in the vertebrate developing retina, 19,20 we found that the SA-β-GAL histochemical staining pattern correlates strongly in the presence of lysosomes in the NbL of the central retina ( Figure 1I-K).…”
Section: Resultsmentioning
confidence: 99%
“…They progressively invaded the ONL and were found near the nuclei of degenerating photoreceptors, suggesting that they were phagocyting cell debris released during photoreceptor degeneration. Macrophages and microglial cells are highly phagocytic and participate in the removal of cell debris during development of the visual system (Hume et al, 1983;Martín-Partido and Navascués, 1990;Egensperger et al, 1996;Moujahid et al, 1996;Rodríguez-Gallardo et al, 2005;Santos et al, 2008;Bejarano-Escobar et al, 2011). Furthermore, retinal microglia are activated in response to nearly all pathological stages of the retina (Langmann, 2007), with microglial cells migrating to the layers affected by degeneration.…”
Section: Microglia In the Experimental Tench Retinal Tissuementioning
confidence: 99%
“…Furthermore, retinal microglia are activated in response to nearly all pathological stages of the retina (Langmann, 2007), with microglial cells migrating to the layers affected by degeneration. Thus, the adult ONL which is normally devoid of microglial cells Santos et al, 2008;Bejarano-Escobar et al, 2011), is colonized by these cells in conditions of photoreceptor degeneration during normal development (Bejarano-Escobar et al, 2011) or under pathological or experimental conditions (Roque et al, 1996;Ng and Streilein, 2001;Harada et al, 2002;Hughes et al, 2003;Zeiss and Johnson, 2004;Zeng et al, 2005;Bailey et al, 2010;Santos et al, 2010).…”
Section: Microglia In the Experimental Tench Retinal Tissuementioning
confidence: 99%
“…Recent studies conducted in our laboratory confirmed the presence of the LIM-domain transcription factor Isl1 in differentiating and mature ganglion, amacrine, bipolar, and horizontal cells in the retina of mammals [54], birds [18], reptiles [12], and fish [911]. In the present study, we extend our observations to the retina of the anuran Xenopus laevis , an amphibian model extensively used in studies of retinal cell organization [44, 55–57].…”
Section: Discussionmentioning
confidence: 78%
“…Surprisingly, strong SV2 immunoreactivity was also found in the scleralmost part of the neuroepithelium, suggesting that differentiating cells were also located in this region (Figure 4(c)). Therefore, we used a polyclonal antibody against bovine rod opsin (CERN-922) that has been described as an excellent photoreceptor marker in fish [911, 5053], reptiles (unpublished observations), birds (unpublished observations), and mammals [54]. A similar antibody has been previously used to identify rod photoreceptors in the developing X. laevis retina [45].…”
Section: Resultsmentioning
confidence: 99%